Facial expression recognition based on luminance sticker - Marimuthu, Satiyan (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2012)
The objectives of this research on facial expression recognition are to acquire facial action unit data, to propose feature extraction algorithms for facial expression recognition, to select the best statistical feature for the classification techniques, to propose artificial intelligences based techniques for the classification of facial expressions and to compare and evaluate the performance of the suggested methods.